2003
DOI: 10.1037/0022-006x.71.4.821
|View full text |Cite
|
Sign up to set email alerts
|

Group cognitive-behavioral therapy for generalized anxiety disorder: Treatment outcome and long-term follow-up.

Abstract: A recently developed cognitive-behavioral treatment for generalized anxiety disorder (GAD) targets intolerance of uncertainty by the reevaluation of positive beliefs about worry, problem-solving training, and cognitive exposure. As previous studies have established the treatment's efficacy when delivered individually, the present study tests the treatment in a group format as a way to enhance its cost-benefit ratio. A total of 52 GAD patients received 14 sessions of cognitive-behavioral therapy in small groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
142
4
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(175 citation statements)
references
References 10 publications
16
142
4
13
Order By: Relevance
“…There is considerable evidence that intolerance of uncertainty (IU) is a cognitive vulnerability factor for worry (Koerner & Dugas, 2008;Ladouceur, Gosselin, & Dugas, 2000; Mediators of repetitive negative thinking 4 Sexton, Norton, Walker, & Norton, 2003;van der Heiden, Melchior, Muris, Bouwmeester, Bos, & van der Molen, 2010) and an important maintaining factor for GAD (Behar, DiMarco, Hekler, Mohlman, & Staples, 2009;Dugas, Gagnon, Ladouceur, & Freeston, 1998). Intervention trials have found that changes in IU are associated with improvements in worry and anxiety symptoms during cognitive behavioral therapy (CBT, Dugas et al, 2003;Dugas et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that intolerance of uncertainty (IU) is a cognitive vulnerability factor for worry (Koerner & Dugas, 2008;Ladouceur, Gosselin, & Dugas, 2000; Mediators of repetitive negative thinking 4 Sexton, Norton, Walker, & Norton, 2003;van der Heiden, Melchior, Muris, Bouwmeester, Bos, & van der Molen, 2010) and an important maintaining factor for GAD (Behar, DiMarco, Hekler, Mohlman, & Staples, 2009;Dugas, Gagnon, Ladouceur, & Freeston, 1998). Intervention trials have found that changes in IU are associated with improvements in worry and anxiety symptoms during cognitive behavioral therapy (CBT, Dugas et al, 2003;Dugas et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, se conocen investigaciones que evidencian resultados satisfactorios obtenidos con tratamientos grupales para trastornos específicos de ansiedad (Ballester y Botella, 1992;Dugas et al, 2003). Sin embargo, no se han encontrado estudios que hayan integrado en un mismo protocolo de evaluación y tratamiento el abordaje grupal de distintos trastornos y procedimientos terapéuticos.…”
Section: Discussionunclassified
“…This is accomplished with the use of treatment strategies (such as behavioural exposure to uncertainty, problem-solving training and imaginal exposure) that aim to help patients confront uncertainty-inducing thoughts and situations. The treatment has been tested in four published randomised clinical trials, with results showing that it is more efficacious than a waiting list control, 34,35 supportive therapy 36 and applied relaxation. 37 The findings also show that 60-77% of patients attain GAD remission and that 50-55% achieve high-end state functioning following the treatment.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%